Vector-IM-based assessment of alternative framing systems under bi-directional ground-motion. (1st February 2017) - Málaga-Chuquitaype, C.; Bougatsas, K.
Highlights: Detailed probabilistic assessment of the response of alternative 3D framing systems subjected to bi-directional loading. Vector-valued and scalar based formulations compared and benefits of vector analysis quantified. Reductions in dispersion of up to 40% at larger drifts possible with adequate IM-vector definition. Consistently lower drift hazards experienced by one-way frames in comparison with two-way systems. Results useful to discern the framing system with better performance at different deformation levels. Abstract: This paper examines the seismic performance of steel buildings with alternative framing systems subjected to bi-directional ground-motion. Peak drifts of one-way (perimeter framing) and two-way (space framing) systems are assessed by means of scalar and vector-valued probabilistic methods. Extensive non-linear response history analyses over idealized 3D structures representing 6- and 9-storey buildings are performed under pairs of linearly scaled ground-motions. Both far-field and near-field non-pulselike acceleration series are considered. The spectral acceleration of the geometric mean of the two horizontal components ( S a, GM ) is taken as the primary intensity measure (IM) while four other ground-motion parameters are employed to construct IM-vectors including: the spectral acceleration ratio ( R T 3, T 1 ), the spectral shape parameter ( N p ), and two frequency content parameters ( T m and T o ). This paper shows that incorporating the vector 〈 S a, GM, N p 〉 into the assessment of bi-directionally loaded 3D buildings yields up to 40% lower conditional standard deviations than a purely scalar formulation at large drift levels while the vector 〈 S a, GM, R T 3, T 1 〉 is more efficient at smaller drifts. The effects of alternative framing systems on structural fragilities are found to differ depending on the number of storeys. For 6-storey structures, consistently higher capacities are observed in two-way layouts with respect to one-way systems but they are associated with increasing variabilities at larger demand levels. Conversely, the 9-storey two-way building experiences 5% lower mean capacities than its one-way counterpart. Finally, drift hazard curves are calculated by combining the building fragilities with idealized ground-motion hazard estimates. The results indicate that one-way buildings experience consistently lower drift exceedance rates regardless of the ground-motion type, especially for drift levels larger than 2% although the differences are larger for the 9-storey frames in comparison with their 6-storey counterparts. This study represents a first attempt to implement vector-valued analysis in the context of bi-directionally loaded structures and its results constitute an important step towards discerning the most favourable framing system at different seismic performance levels.